PENGARUH HYGIENE MAKANAN TERHADAP KUALITAS MAKANAN BREAKFAST PADA RESTORAN THE AXANA HOTEL PADANG - Fitri, Denisa; Asnur, Lise (Jurnal Daya Saing, 2023)
The purpose of this study was to analyze the effect of food hygiene on food quality at The Axana Hotel Padang. This type of quantitative research with a causal relationship approach. The sampling method is non-probability sampling using saturated sampling. The research instrument is a questionnaire equipped with Likert scale. From the results of the study it was concluded that food hygiene (X) showed a percentage of 41% in the range ≥ 69 - < 70 included in the good category. food quality (Y) shows a percentage of 53% in the range ≥ 40 - < 41 included in the good category. Simple linear regression test with the T test on the food hygiene variable affects the food quality variable at The Axana Hotel Padang. The F test value of the food hygiene variable (X) has a significant effect on the quality of food at The Axana Hotel Padang. Adjustment value. R square of 0.284 means that the food hygiene variable has an effect of 28.4% on the quality of food at The Axana Hotel Padang and 71.6% is influenced by other variables. Keywords: food hygiene, food quality, The Axana Hotel Padang